A Novel Anti-maloperation Gas Relay for Internal Fault Protection of Oil-immersed Transformers - Xue, Bing; Yi, Wanshuang; Li, Yongbo; Liu, Chengxiang; Tian, Siyu; Ma, Jinyang; Zhang, Tengbo; Wan, Shuting (Advances in Electrical and Computer Engineering, 2025)
The gas relay is an essential non-electric protection device in oil-immersed transformers. Due to the single triggering mode of heavy gas alarm and external faults, gas relay may cause misoperation of heavy gas. A method for preventing misoperation based on gas relay baffle angle information and the differential current signal is proposed, and an intelligent anti-misoperation gas relay is designed. Based on angle sensors and Hall current sensors, the gas relay was improved and designed. According to the performance comparison and analysis of the improved performance, a modified scheme based on Hall current sensors was selected to measure the angle of the baffle. The combination of baffle angle information and relay signal was used to determine whether the heavy gas signal was a false alarm. Based on differential current signals, the type of transformer faults can be determined to avoid false alarms of heavy gas caused by faults outside the area. A new type of anti-misoperation gas relay developed by combining two anti-misoperation strategies can not only output heavy gas misoperation types but also monitor the real-time operation status of transformers. Index Terms--anti-maloperation gas relay, baffle angle, differential current, heavy gas alarm, oil-immersed transformer.